Paper Spray Mass Spectrometry Analysis of Forensics Evidence: AComprehensive Guide - Vinny Sharma; Saijal Varishney; Shruti Jindal (Indian Journal of Forensic Medicine and Pathology, 2025)
Advancements in chemical instrumentation have sparked interest in using micro samples for medical and translational research. Paper substrates are widely used for collecting bio-Áuids, and the recommended technique is mass spectrometryor analyzing dried blood spot (DBS) samples. Paper spray offers as a substitute for conventional chromatography and sample preparation, allowing for the process of ionizing various molecules from complex bio-Áuids with high sensitivity. Thismakes paper spray a promising option to quickly analyze data at the point of care (POC) without requiring lengthy separation processes. With further development for the rapid detection of metabolites, medicinal drugs, and illicit drugs, paper spray has the potential to replace intricate analysis procedures due to its uniformity and standardization. Surface and substrate modi𿿿cations can enhance desorption andionizationef𿿿ciencies, leading to improved sensitivity. Lipid and metabolite analysis canbe thoroughly examined using paper spray ionization mass spectrometry, which is already being used in clinical settings. As a high-throughput, fully automated method for preliminary testing of polar compounds banned from sports, paper spray mass spectrometry was investigated in a proof-of-concept study. Paper spray mass spectrometry reduces preparation time and costs signi𿿿cantly by doing away with chromatographic separation and sample preparation